Conceptualising the future of HRM and technology research - Bondarouk, Tanya; Brewster, Chris (Taylor & Francis, 2016)
This paper examines the role of information technology (IT) directly on one central aspect of work in the twenty-first century, its impact on HRM itself. We use the long-established ‘Harvard’ model of HRM, offering a more contextualised view of HRM, a more expansive view of stakeholders, and a wider and more long-term approach to outcomes. Applying those principles to the literature on IT and HRM helps us clarify both the advantages and disadvantages to different stakeholders of the intersection between HRM and technology. We show that rapid technological developments offer a new, smart, digital context for HRM practices with the better quality HRM data and enabling a strong HRM ownership by all stakeholders. At the same time, we see a tension in HRM responsibilities between HRM professionals and organizational members who are not directly assigned HRM tasks but are the subject of them. On the basis of that analysis we offer suggestions for future research.
Keywords: contextual HRM; e-HRM; Harvard approach; HRM outcomes; human resource management; information technology; multi-stakeholder perspective; human resource management; personnel administration; enterprises; data systems; subsidiary companies; recruitment of employees; employees; leadership (activity); human resources; business; fi=Johtaminen ja organisaatiot|en=Management and Organization|